2022
DOI: 10.1186/s12885-022-09686-y
|View full text |Cite
|
Sign up to set email alerts
|

YAP1 is essential for malignant mesothelioma tumor maintenance

Abstract: Malignant pleural mesothelioma, a tumor arising from the membrane covering the lungs and the inner side of the ribs, is a cancer in which genetic alterations of genes encoding proteins that act on or are part of the Hippo-YAP1 signaling pathway are frequent. Dysfunctional Hippo signaling may result in aberrant activation of the transcriptional coactivator protein YAP1, which binds to and activates transcription factors of the TEAD family. Recent studies have associated elevated YAP1 protein activity with a poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…SLC39A1 encodes a zinc transporter and is a known tumor suppressor gene controlled by YAP, part of the Hippo pathway 34 . The Hippo pathway is known to be dysregulated in mesothelioma and therefore loss of this gene is potentially a driver of mesothelioma 35 . Because the two fusion events breakpoints in SLC39A1 are slightly different, and the two fusion events involve breakpoints in different members of the ATP1A family, two distinct inversions on both homologous chromosomes is possible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SLC39A1 encodes a zinc transporter and is a known tumor suppressor gene controlled by YAP, part of the Hippo pathway 34 . The Hippo pathway is known to be dysregulated in mesothelioma and therefore loss of this gene is potentially a driver of mesothelioma 35 . Because the two fusion events breakpoints in SLC39A1 are slightly different, and the two fusion events involve breakpoints in different members of the ATP1A family, two distinct inversions on both homologous chromosomes is possible.…”
Section: Resultsmentioning
confidence: 99%
“…34 The Hippo pathway is known to be dysregulated in mesothelioma and therefore loss of this gene is potentially a driver of mesothelioma. 35 Because the two fusion events breakpoints in SLC39A1 are slightly different, and the two fusion events involve breakpoints in different members of the ATP1A family, two distinct inversions on both homologous chromosomes is possible. However, one event involving a single inversion followed by a deletion on one chromosome, is more likely (Figure 3).…”
Section: Identification Of Truncal Gene Fusionsmentioning
confidence: 99%
“…After Hippo signaling is inhibited, YAP1 accumulates in the nucleus and interacts with TEAD transcription factors. The activation of the YAP1/TEAD transcriptional regulatory complex induces malignant cancer behaviors, such as promoting cell proliferation and inhibiting cell apoptosis, in a variety of cancers [44] , [45] , [46] . Further research showed that TEAD directly bound to the promoter region of PRIM1, indicating that PRIM1 was a downstream target of the YAP1/TEAD transcriptional regulatory complex.…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo pathway is known to be dysregulated in mesothelioma and therefore loss of this gene is potentially a driver of mesothelioma [35]. Because the two fusion events breakpoints in SLC39A1 are slightly different, and the two fusion events involve breakpoints in different members of the ATP1A family, two distinct inversions on both homologous chromosomes is possible.…”
Section: Identification Of Truncal Gene Fusionsmentioning
confidence: 99%